2018
DOI: 10.1186/s12904-018-0324-2
|View full text |Cite
|
Sign up to set email alerts
|

Building Bridges, Paediatric Palliative Care in Belgium: A secondary data analysis of annual paediatric liaison team reports from 2010 to 2014

Abstract: BackgroundAlthough continuity of care in paediatric palliative care (PPC) is considered to be an essential element of quality of care, it’s implementation is challenging. In Belgium, five paediatric liaison teams (PLTs) deliver palliative care. A Royal Decree issued in 2010 provides the legal framework that defines the PLTs’ missions, as ensuring continuity of curative and palliative care between the hospital and home for children diagnosed with life-limiting conditions. This national study describes how PLTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
0
19
0
4
Order By: Relevance
“…The high proportion of children with CCC who are not referred to PLTs, especially those under 1 year, may be partially explained by the fact that many of these children die before they are discharged from hospital, but also because neonatal palliative care is overlooked in Belgium. Furthermore, a previous study conducted by Friedel et al indicated that from all children followed up annually by PLTs at a nationwide level (n=721), a high proportion of home deaths (51%) occurred for all children who died (n=85) and therefore were neither registered in death hospital databases 13. The maximum number of 721 children followed up annually by the five PLTs in Belgium invalidates therefore the hypothesis according which the high number of patients with a CCC attending Brussels hospitals (n=22 533) may have been referred to PLTs outside Brussels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high proportion of children with CCC who are not referred to PLTs, especially those under 1 year, may be partially explained by the fact that many of these children die before they are discharged from hospital, but also because neonatal palliative care is overlooked in Belgium. Furthermore, a previous study conducted by Friedel et al indicated that from all children followed up annually by PLTs at a nationwide level (n=721), a high proportion of home deaths (51%) occurred for all children who died (n=85) and therefore were neither registered in death hospital databases 13. The maximum number of 721 children followed up annually by the five PLTs in Belgium invalidates therefore the hypothesis according which the high number of patients with a CCC attending Brussels hospitals (n=22 533) may have been referred to PLTs outside Brussels.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in 2015, the International Classification of Diseases, Ninth Revision (ICD-9) classification changed in Belgium to ICD-10. Third, the only published study on the number of children referred to PLTs in Belgium was based on the same 5-year period 13…”
Section: Methodsmentioning
confidence: 99%
“…Between 2009 and 2014, 61% of our patients died at home [ 14 ], and a similar tendency is visible for the period between 2016 and June 2019 (58%). In the corresponding literature, this number is also reported around 50% [ 7 , 9 , 15 ]. With the help of SAPPV, dying under adequate symptom control outside a hospital setting seems feasible.…”
Section: Discussionmentioning
confidence: 96%
“…In Europe, various palliative care services have been developed over the last two decades, which can be found in different sectors and are divided into hospitals, autonomous installations, or home services. 19 However, there is still no consensus as to which of these offers the best continuation of care. 20 We also observed the impact of HCS in assisting children with invasive HMV for the release of hospital beds.…”
Section: Discussionmentioning
confidence: 99%